Agricultural Value Added and Economic Development in the CEMAC Zone - Fidelis Mbotiji; Saidou Baba Oumar; Bime Mary Juliet Egwu (Law and Economy, 2023)
Sustained economic growth and development is an important economic policy objective to all economies in the world. It is even more important for countries of the CEMAC sub-region whose development index remains very low. Sustained economic growth is therefore the surest means to fight against poverty and move the economies of CEMAC member countries towards emergence. Using data from 1990 to 2020, this study examines the effect of agricultural value added on economic development within the CEMAC economies. Data was scrutinized for stationarity using the Levin Lin Chu (LLC). Furthermore, the panel fixed effect, Random effect and the generalised least square techniques were used to examine the effect of agricultural value added on economic development of economies within the CEMAC zone. The result shows that, agricultural value added has a positive effect on economic development, implying that there is a direct and significant relationship between agricultural value added and economic development. Precisely, indicating that the further a country within the CEMAC subregion enhances agronomic transformation, the better it levels of economic development. Policy recommendation are equally discussed.